Soluble epoxide hydrolase: Gene structure, expression and deletion - Harris, Todd R. (2013)
Mammalian soluble epoxide hydrolase (sEH) converts epoxides to their corresponding diols through the addition of a water molecule. sEH readily hydrolyzes lipid signaling molecules, including the epoxyeicosatrienoic acids (EETs), epoxidized lipids produced from arachidonic acid by the action of cytochrome p450s. Through its metabolism of the EETs and other lipid mediators, sEH contributes to the regulation of vascular tone, nociception, angiogenesis and the inflammatory response. Because of its central physiological role in disease states such as cardiac hypertrophy, diabetes, hypertension, and pain sEH is being investigated as a therapeutic target. This review begins with a brief introduction to sEH protein structure and function. sEH evolution and gene structure are then discussed before human small nucleotide polymorphisms and mammalian gene expression are described in the context of several disease models. The review ends with an overview of studies that have employed the sEH knockout mouse model.